Adult attachment and dehumanization among Chinese college students: trait attachment and state attachment perspectives - Guo, Minna; Xu, Beibei; Wang, Haiyao; Le, Thi Quynh Mai; Yan, Zhihao; Sang, Qingsong (Frontiers in Psychology, 2024)
Current social issues such as bullying, online violence, and local conflicts are all hot topics in the field of psychology, and these phenomena are related to dehumanization, but research on dehumanization from a non-western background has been rare. As a key factor influencing individual behavior, attachment has not been incorporated into the relevant research on dehumanization.Therefore, this study presented empirical evidence to explore the relationship between adult attachment (both trait and state) and dehumanization, the samples were college students from China.In Study 1 (N=705), latent profile analysis was employed to identify four types of adult attachment: preoccupied, secure, fearful, and dismissing. The study revealed that these different attachment types have varying impacts on dehumanization. Study 2 (N=281) focused on activating secure attachment and examined the effects of three state attachment types-security, avoidance, and anxiety-on dehumanization. The findings showed that both security and avoidance predict dehumanization. This research established a link between adult attachment and dehumanization, offering new insights into the psychological mechanisms underlying dehumanization. It also suggests new approaches for the prevention and intervention of dehumanization.